Inventing human rights : a history - Hunt, Lynn Avery (New York ; London : W. W. Norton, 2008)
In this extraordinary work of cultural and intellectual history, Hunt grounds the creation of human rights in the changes that authors brought to literature, the rejection of torture as a means of finding out truth and the spread of empathy.
"Torrents of emotion" : reading novels and imagining equality -- "Bone of their bone" : abolishing torture -- "They have set a great example" : declaring rights -- "There will be no end of it" : the consequences of declaring -- "The soft power of humanity" : why human rights failed, only to succeed in the long run.
Originally published: 2007.
Includes bibliographical references and index.
Keywords: Human rights -- History; Human rights in literature; Torture -- History